Influence of demographic factors on the public pension spending - Radu Ciobanu (Budgetary Research Review (BRR), 2014)
Demographic aging is a global phenomenon encountered especially in the developed states and is manifesting by the increase the share of people aged over 60-65 years in total population, a process that will affect all areas of the world in this century. In the coming decades, population aging will put pressure on public spending in areas such as pensions and health care for the population aged 60-65 years. Moreover, the need to increase the share of these spending in total public expenditures will generate big problems in a way that budgets for other areas may suffer considerable discounts. The study aims to analyze the changes that may occur in the structure and volume of spending on social security (pensions) as a result of changes in demographic factors.
Keywords: H51; J11; J14; 330; demographic aging; social security spending; demographic factors; budget